Establishing an Ocean Acidification Monitoring System for the Tropical Waters of Indonesia Facing Regional Climate Variability - Hanif Budi Prayitno; Rachma Puspitasari; Suppakarn Jandang; Karlina Triana; Edwards Taufiqurrahman; Lestari; Afdal; Ita Wulandari; Harmesa; Hanny Meirinawati; Suci Lastrini; Muhamad Taufik Kaisupy; A'an Johan Wahyudi (Universitas Gadjah Mada, 2020)
The emission of greenhouse gases, including high CO2 and other materials, initiates global warming and climate change. Atmospheric CO2 that affects the carbonate system of seawater causes ocean acidification (OA). OA affects marine organisms directly, as well as humans economically and ecologically. Considering the high impact of OA and following the United Nations' Sustainable Development Goals, systematic research and monitoring of OA is necessary in Indonesia, whose seas play an important role in this emerging phenomenon. This review discusses the urgency of OA monitoring systems and suggests carbonate system monitoring, as well as carbon biogeochemistry. OA significantly affects marine production and alters ecosystem services, and it is likely to have an impact on habitats shifting from calcified to non-calcified and reducing benthic complexity. Its effect on calcifying organisms can also be found, i.e., coral calcification and/or dissolution of CaCO3 of calcifying organisms. Acidity (pH), as well as the carbonate system variables of seawater, fluctuate, especially with variations in space and time. Coastal ecosystems that are directly affected by terrestrial input will have carbonate system variables that fluctuate more. The annual rate of decreasing seawater pH, especially over an open and large spatial scale, may indicate OA. Therefore, a monitoring system must be implemented to obtain systematic and comprehensive information on OA. Here, we also introduce a biogeochemical monitoring initiative for OA in Lombok with the established protocols. Improvement of many aspects, including analysis instruments, analysis methods, sample treatment, and sampling frequency will provide new insight into further research and monitoring of OA.